Interspecific Niche Competition Increases Morphological Diversity in Multi-Species Microbial Communities - Chu, Xiao-Lin; Zhang, Quan-Guo; Buckling, Angus; Castledine, Meaghan (Frontiers in Microbiology, 2021)
Intraspecific competition for limited niches has been recognized as a driving force for adaptive radiation, but results for the role of interspecific competition have been mixed. Here, we report the adaptive diversification of the model bacteria Pseudomonas fluorescens in the presence of different numbers and combinations of four competing bacterial species. Increasing the diversity of competitive community increased the morphological diversity of focal species, which is caused by impeding the domination of a single morphotype. Specifically, this pattern was driven by more diverse communities being more likely to contain key species that occupy the same niche as the otherwise competitively superior morphotype, and thus prevent competitive exclusion, within the focal species. Our results suggest that sympatric adaptive radiation is driven by the presence or absence of niche-specific competitors.